Opus Posthumous and Other Poems - Slavitt, David R., 1935- (Book collections on Project MUSE., 2021)
"As he prepares to enter his sixth decade of publishing poetry, David R. Slavitt, whose debut book of verse appeared in 1961, remains a determined wildcatter who ranges as far as he thinks necessary to drill for meaning, wherever and however he can get it. Traversing Africa, India, Israel, and the America in which he finds himself, Slavitt's new collection visits zoos, casinos, baseball fields, and cemeteries searching for clues from which he might learn at least a little. He translates verse from Yiddish and Provencal and offers commentaries on received wisdom, everyday events, and the vagaries of existence. With "Opus Posthumous"-the title is a joke, as he remains very much alive-Slavitt presents an august work possessed of a richness toward which he has worked throughout his long life. By turns wry, erudite, and dyspeptic, this new volume offers ample rewards of his maturity"--